2014
DOI: 10.1159/000357757
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Vaginal Birth after Cesarean Section: A Cohort Study

Abstract: Objective: To develop a model to predict vaginal birth after cesarean (VBAC) in our population and to compare the accuracy of this model to the accuracy of a previously published widely used model. Materials and Methods: Women attempting trial of labor after cesarean delivery (TOLAC) at our institution from January 1, 2000 through May 30, 2010 were evaluated for inclusion. Demographic and clinical data were collected. Associations of these characteristics with VBAC were evaluated with univariate and multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 24 publications
5
43
1
Order By: Relevance
“…Rates of VBAC success have consistently been quoted to range between 60 and 80%, with most averaging~70%. 2,5,10,20 Our study noted a significantly lower VBAC success rate of~48.0%, which included deliveries both with and without instrumentation. Some of the best predictors of successful VBAC delivery remain a history of prior successful vaginal delivery, 3,19 and/or prior successful VBAC delivery.…”
Section: Discussionmentioning
confidence: 71%
“…Rates of VBAC success have consistently been quoted to range between 60 and 80%, with most averaging~70%. 2,5,10,20 Our study noted a significantly lower VBAC success rate of~48.0%, which included deliveries both with and without instrumentation. Some of the best predictors of successful VBAC delivery remain a history of prior successful vaginal delivery, 3,19 and/or prior successful VBAC delivery.…”
Section: Discussionmentioning
confidence: 71%
“…In this study, BMI was significantly lower in the successful TOLAC group compared to the unsuccessful group, and the number of women with BMI >25 kg/m 2 was significantly higher in the unsuccessful group; also, mean gestational age was significantly lower in the successful TOLAC group compared to the unsuccessful group, and the number of women admitted in labor with gestation ≥40 weeks was significantly higher in the unsuccessful group. Landon et al (17) reported a significantly lower success rate of vaginal birth after cesarean section (68.4%) in obese (BMI ≥30) than non-obese women (76.9%), and Juhasz et al (18) reported decreasing chances of a successful TOLAC with increasing BMI; also, Tessmer et al (19) concluded that VBAC success was independently associated with age <30 years, body mass index <30, prior vaginal delivery, and prior VBAC. Smith et al (20) concluded that a TOLAC was likely to be unsuccessful at 41 weeks or 42 weeks gestation compared to a TOLAC at 40 weeks, and Coassolo et al (21) reported a 31.3% TOLAC failure rate at 40 weeks or beyond, against 22% in <40 weeks; also, Tita et al (22) concluded that the risks of maternal morbidities and cesarean delivery, but not neonatal morbidity, increased significantly among laboring nulliparous women beyond 39 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…A number of risk factors for unsuccessful VBAC are mentioned like induced labor, no previous vaginal birth, body-mass index greater than 30, and previous cesarean section for dystocia [19][20][21][22][23] . A study done on Fourteen thousand five hundred twenty-nine women found out that overall Trial of Labour after one previous cesarean section success rate in obese women (BMI≥30) was lower (68.4%) than in nonobese women (BMI<30) 24 .Similar results were seen in our study.…”
Section: Discussionmentioning
confidence: 99%